Заметки о древнейших названиях Фракии - Чередниченко, А. Г. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryA. Cherednichenko. Notes on the Ancient Names of the ThraceThe article is devoted to the problem of origin of the ancient names of the Thrace: Πέρκη [χώρα] ‘country of oaks’ and ’Αρία ‘country of the best, noble, free people’ or ‘country of oracles’. These names marked lands in the North of the Aegean Region, which were inhabited by various Indo-European and Non-Indo-European tribes in the II m. B. C. In addition it is possible to suggest the hypothesis on the origin of the ethnos Θρ´κες from the South of the Balkan Peninsula.Key words: ethno-cultural history, palaeo-onomastics, etymology, the Indo-Europeans, the Thrace.